Titanium alloys surface integrity of belt grinding considering different machining trajectory direction - Jiang, Guiyun; Yang, Hang; Xiao, Guijian; Zhao, Zeyong; Wu, Yuan (Frontiers in Materials, 2022)
The interplay of abrasive grains and materials complicates the grinding of titanium alloys by abrasive belts. Notably, the influence relationship of surface generation for complex curved workpieces such as hollow blades needs to be clarified, making precise control of the surface integrity of complex surfaces difficult in abrasive belt grinding applications. This paper thus proposes a trajectory planning method based on the direction of interaction between grinding grains and materials to reveal its influence law on the surface integrity of complex curved surfaces of titanium alloy with unevenly distributed machining allowances. First, a machining trajectory with different angles between the grinding direction and feed direction is proposed. In order to determine the corresponding experimental scheme for titanium alloy hollow blades. Experimental results are used to analyze the influence of different grinding trajectory directions on the surface roughness, residual stress, surface topography, and accuracy of the contours. The results show that different grinding trajectory directions significantly affect the workpiece’s surface integrity. By varying the grinding trajectory direction, it is possible to reduce the surface roughness of titanium alloy workpieces by approximately 40%, increase the surface residual compressive stress by approximately 50%, provide a finer workpiece surface and improve the consistency of the surface texture. This work is expected to guide the efficient and high-quality machining of complex curved parts such as titanium alloy hollow blades.